Producción y comercialización de embutidos vegetarianos libres de gluten desde Ecuador hacia Reino Unido - Prado Sola, Stephanny Carolina (2018)
The present business plan, seeks to take advantage of the properties offered by quinoa in nutrition. NOA, is a product that stands out for providing proteins and vitamins that help improve food by substituting meat foods that today contain high toxicity index caused by bad production practices. In Ecuador, the production of this cereal has increased substantially, because the objective is to improve international competitiveness. In addition, the incentive of the industrialization projects such as tax exemption, preferential zones in production costs, allows to create new products in international markets, consequently Ecuador can become known as a competitive country with products that contain greater added value. Nowadays, health care trends increase substantially due to the awareness for a better lifestyle. Eating habits are an important factor, since the business idea is based on offering a better product, in terms of nutrition, it can substitute meat products, without changing the intake, in this case, of sausages. NOA gluten-free sausages will be marketed in London-UK through supermarket chains, the UK is one of the 10 countries with the best income level around the world with a GDP of 2.6 billion dollars. The vegetarian population represents around 8% of the total population, therefore it is an attractive market for the exports products, because the project profits significant margins, which reflects a NPV of $ 93,678.70 and an IRR of 69.73%. In addition, it maintains cash flows that allow it to cover operations activities, sales generate 14% profit at the end of the financial year.